2015
DOI: 10.1007/s10461-015-1246-0
|View full text |Cite
|
Sign up to set email alerts
|

Which Psychological Factors are Related to HIV Testing? A Quantitative Systematic Review of Global Studies

Abstract: Deciding to test for HIV is necessary for receiving HIV treatment and care among those who are HIV-positive. This article presents a systematic review of quantitative studies on relationships between psychological (cognitive and affective) variables and HIV testing. Sixty two studies were included (fifty six cross sectional). Most measured lifetime testing. HIV knowledge, risk perception and stigma were the most commonly measured psychological variables. Meta-analysis was carried out on the relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
76
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 156 publications
6
76
1
1
Order By: Relevance
“…This worry over anticipated stigma has been previously reported as a deterrent to HIV testing (Leblanc, Flores, & Barroso, 2016) and underscores the need for offering confidential services and reassuring clients about the confidentiality of test results. Consistent with other studies (Evangeli, Pady, & Wroe, 2016). we also found that other psychological impediments such as fear of an HIV-positive diagnosis or perceiving themselves at low risk for HIV infection could be barriers to HCT, and these may be compounded among WIC participants experiencing perinatal depression.…”
Section: Discussionsupporting
confidence: 93%
“…This worry over anticipated stigma has been previously reported as a deterrent to HIV testing (Leblanc, Flores, & Barroso, 2016) and underscores the need for offering confidential services and reassuring clients about the confidentiality of test results. Consistent with other studies (Evangeli, Pady, & Wroe, 2016). we also found that other psychological impediments such as fear of an HIV-positive diagnosis or perceiving themselves at low risk for HIV infection could be barriers to HCT, and these may be compounded among WIC participants experiencing perinatal depression.…”
Section: Discussionsupporting
confidence: 93%
“…It may be, however, that affect is another important determinant of many HIV-related behaviours. For example, consistent relationships between fear of HIV and HIV testing on the one hand and HIV testing itself on the other hand, have been reported [29]. It may also be that affect (particularly anxious affect) plays a key role in driving many HIV disclosure decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The approach of drawing on theoretical models relating to affect rather than of heath behaviour is novel in the HIV context. For example, the Health Belief Model [28] was the most commonly used model used in a recent review of psychological correlates of HIV testing [29], and the Information Motivation Behavioural Skills Model [30] (based on the Theory of Planned Behaviour [31]) has guided much recent research on antiretroviral adherence. Such models primarily outline cognitive determinants of behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…This may have been, in part, due to a lack of awareness about HIV risk. Research has shown a link between risk knowledge and HIV-testing behavior (Evangeli et al, 2016), but studies are needed to examine how risk knowledge specific to IPV impacts HIV testing in this population. Futures Without Violence provides several free resources about the intersection of HIV and IPV targeting both patients and providers (Futures Without Violence, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified numerous barriers to HIV testing including fear, stigma, lack of knowledge about risk factors, treatment options and costs, and difficulty accessing/navigating the health care system (Evangeli, Pady, & Wroe, 2016; Messer et al, 2013; Schwarcz et al, 2011). Additional barriers exist for individuals with a history of IPV such as fear of subsequent violence from partners, social isolation that further limits the individual’s ability to access care, and a lack of knowledge on the part of many providers to identify individuals with a history of victimization and link them to appropriate services, including HIV testing (Draucker et al, 2015; Maher et al, 2000; Rountree, 2010).…”
mentioning
confidence: 99%